Family-Centered Care Experiences in Elderly with Chronic Diseases in Communities: Qualitative Study of Patients, Families, Nurses, and Volunteers - Ah Yusuf; Jenny Marlindawani Purba; Dewi Eka Putri; Ronal Surya Aditya; Abdullah Saleh Alruwaili; Daifallah M. AlRazeeni (Health Equity)
Introduction: The family, at community, must be an important part of elderly care. However, most of the elderly experience a decrease in psychological well-being and quality of life. This is not in accordance with the concept of the family-centered care (FCC) model and can endanger the continuity of the elderly with chronic illnesses. Objective: The aim of this study was to explore experience of FCC among patients with chronic illness, nurses, families, and volunteers. Methods: This study examines the contextual-based FCC model qualitatively. In-depth interviews and focus group discussions were conducted by 12 elderly people, 3 nurses, 10 family members, and 3 volunteers. In total, 36 people, where several were FGD participants, were also interviewed in depth. Data were analyzed using thematic analysis, with codes organized into larger themes. Result: In total, 36 interviews and FGDs were conducted. The concept of information interaction, the phenomenon of emotional interaction, the practical interaction, and various factors that can either facilitate or impede interaction, were considered the four significant themes. Conclusion: FCC acceptance is found in interactions between parents, nurses, family, and volunteers who are not optimistic. Lack of communication and collaboration was noted between community nurses and volunteers. Offer a new perspective on developing and implementing interventions that facilitate positive interactions, reduce family burdens, provide high-quality treatment for parents with chronic diseases, and improve the quality of care for those with advanced chronic conditions. Recommendation: These insights provide a fresh perspective on how to develop and implement effective interventions in this context. It is recommended that future research should employ multiple methodologies to investigate FCC across diverse health practices for the elderly population.